DNA Barcode-Based PCR-RFLP and Diagnostic PCR for Authentication of Jinqian Baihua She (Bungarus Parvus). (19th May 2015) - Li, Xiaolei; Zeng, Weiping; Liao, Jing; Liang, Zhenbiao; Huang, Shuhua; Chao, Zhi
Abstract : We established polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and diagnostic PCR based on cytochrome C oxidase subunit I (COI) barcodes of Bungarus multicinctus, genuine Jinqian Baihua She (JBS), and adulterant snake species. The PCR-RFLP system utilizes the specific restriction sites of Spe I and Bst EII in the COI sequence of B. multicinctus to allow its cleavage into 3 fragments (120 bp, 230 bp, and 340 bp); the COI sequences of the adulterants do not contain these restriction sites and therefore remained intact after digestion with Spe I and Bst EII (except for that of Zaocys dhumnades, which could be cleaved into a 120 bp and a 570 bp fragment). For diagnostic PCR, a pair of species-specific primers (COI37 and COI337) was designed to amplify a specific 300 bp amplicon from the genomic DNA of B. multicinctus ; no such amplicons were found in other allied species. We tested the two methods using 11 commercial JBS samples, and the results demonstrated that barcode-based PCR-RFLP and diagnostic PCR both allowed effective and accurate authentication of JBS.